Left Anterior Fascicular Block After Transcatheter Closure of Ventricular Septal Defect in Children - Wu, Zhijun; Yang, Penghui; Xiang, Ping; Ji, Xiaojuan; Tian, Jie; Li, Mi (Frontiers in Cardiovascular Medicine, 2021)
Background: Arrhythmia is the most common complication after transcatheter closure of a ventricular septal defect (VSD). However, the effects of postprocedural left anterior fascicular block are not clear. This study presents the clinical characteristics, prognosis, and related risk factors of left anterior fascicular block after transcatheter closure of a VSD in children. Methods: The clinical and follow-up data of the patients in the Heart Center of Children's Hospital of Chongqing Medical University from June 2009 to October 2018 were reviewed. And 30 cases were eligible out of all 1,371 cases. Results: An electrocardiogram showed a left anterior fascicular block within 3 days, and most patients gradually returned to normal within 1–2 years, showing a dynamic change. Left ventricular end-diastolic dimension Z-score ranged from −2 to 2 in all children, and no decrease of left ventricular ejection fraction was found in all children. The high ratio between VSD size and body surface area [p < 0.05, odds ratio (OR) 2.6, 95% CI: 1.136–6.113] and large diameter difference between the occluder size and VSD size (p < 0.05, OR 2.1, 95% CI: 1.036–4.609) were independent risk factors for postprocedural left anterior fascicular block. Conclusions: The incidence of postprocedural left anterior fascicular block is not that low, and the overall prognosis is quite good at the current follow-up stage. No progressive severity has been found, such as complete left bundle branch block, double (triple) bundle branch block, and atrioventricular block, to have an influence on cardiac systolic and diastolic function.